2012
DOI: 10.1021/jm2017144
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Trypanosomicidal Activity of Pyrazole-Containing Macrocyclic and Macrobicyclic Polyamines: Their Action on Acute and Chronic Phases of Chagas Disease

Abstract: The in vitro and in vivo anti- Trypanosoma cruzi activity of the pyrazole-containing macrobicyclic polyamine 1 and N-methyl- and N-benzyl-substituted monocyclic polyamines 2 and 3 was studied. Activity against both the acute and chronic phases of Chagas disease was considered. The compounds were more active against the parasite and less toxic against Vero cells than the reference drug benznidazole, but 1 and 2 were especially effective, where cryptand 1 was the most active, particularly in the chronic phase. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…1). Macrobicyclic polyamine 1 (Lamarque et al 2001), macrocyclic polyamines 2 and 3 (Arán et al 1999; Kumar et al 2001), with N-methyl- and N-benzyl-substituted pyrazole rings, and macrocyclic analogue 4 (Miranda et al 2004), with bulky octyl groups attached to the amine nitrogens on the side-chains had been previously tested by us against Trypanosoma cruzi (Sánchez-Moreno et al 2012 a ). In those assays it was found that compounds 1 – 3 were more active against the parasite and less toxic against Vero cells than the reference drug benznidazole (BZN), whereas the behaviour of 4 was similar to that of BZN or even worse.…”
Section: Introductionmentioning
confidence: 99%
“…1). Macrobicyclic polyamine 1 (Lamarque et al 2001), macrocyclic polyamines 2 and 3 (Arán et al 1999; Kumar et al 2001), with N-methyl- and N-benzyl-substituted pyrazole rings, and macrocyclic analogue 4 (Miranda et al 2004), with bulky octyl groups attached to the amine nitrogens on the side-chains had been previously tested by us against Trypanosoma cruzi (Sánchez-Moreno et al 2012 a ). In those assays it was found that compounds 1 – 3 were more active against the parasite and less toxic against Vero cells than the reference drug benznidazole (BZN), whereas the behaviour of 4 was similar to that of BZN or even worse.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds tested were the squaramides and acyclic polyamines shown in Table 1. The solutions of the compounds were stored at −20˚C [27] [28]. These squaramides and acyclic polyamines are stable in this medium and can be stored without decomposition for long periods of time.…”
Section: Drugs Testedmentioning
confidence: 99%
“…The antiparasitic activity of squaramides has been demonstrated, also, some showing antimalarial [26] and others antichagasic activity [27]. On the other hand, several macrocyclic scorpiand-like polyamines have proved effective against both the acute and chronic phases of Chagas disease [28].…”
Section: Introductionmentioning
confidence: 99%
“…Use of intracellular forms is more laborious but allow us to obtain more accurate results, as they are transformed into amastigotes in vertebrate host cells. 29 Intracellular assays were performed by infecting macrophage cells with promastigotes, which transformed into amastigotes within 1 day aer infection. Table 1 shows the IC 50 values obtained aer 72 h of exposure to L. infantum, L. braziliensis and L. donovani species.…”
Section: In Vitro Antileishmanial Evaluationmentioning
confidence: 99%
“…The cytotoxicity testing on macrophages was performed by ow cytometric analysis according to a method previously described. 29 The percentage of viable cells was calculated with respect to the control culture. The IC 50 was calculated using linear regression analysis from the K c values of the concentrations employed.…”
Section: Biological Evaluationmentioning
confidence: 99%